2014
DOI: 10.1007/s40069-014-0091-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Prestressed Precast Concrete Bridge Deck Panels Using Damage Plasticity Model

Abstract: This paper describes a three-dimensional approach to modeling the nonlinear behavior of partial-depth precast prestressed concrete bridge decks under increasing static loading. Six full-size panels were analyzed with this approach where the damage plasticity constitutive model was used to model concrete. Numerical results were compared and validated with the experimental data and showed reasonable agreement. The discrepancy between numerical and experimental values of load capacities was within six while the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 7 publications
0
36
0
2
Order By: Relevance
“…It was shown that best results are obtained by small values of viscosity parameter compared to the pseudo time of analysis in the study performed by Lee (1996). Series of guidelines and recommendations are suggested by various researchers in order to consider best values of viscosity parameter in the CDP model depending on the type of predominant internal actions which are active and the degree of nonlinearity that involved in different problems (Wosatko et al (2015), Genikomsou and Polak (2015), Wei Ren et al (2015)). …”
Section:  mentioning
confidence: 99%
“…It was shown that best results are obtained by small values of viscosity parameter compared to the pseudo time of analysis in the study performed by Lee (1996). Series of guidelines and recommendations are suggested by various researchers in order to consider best values of viscosity parameter in the CDP model depending on the type of predominant internal actions which are active and the degree of nonlinearity that involved in different problems (Wosatko et al (2015), Genikomsou and Polak (2015), Wei Ren et al (2015)). …”
Section:  mentioning
confidence: 99%
“…1 Grouted splice of typical configuration used in this study. structural components and structures (Ren et al 2015;Ameli et al 2015). In fact, most of the technical details for this type of product are private and proprietary with restricted access.…”
Section: Introductionmentioning
confidence: 99%
“…1. Ren et al [14] ( 1 ) C is the coefficient of linear expansion (1.0 x 10^-5 MPa/ C); P is the force applied after long-term losses in prestressed beam took place. E is the modulus of elasticity (MPa) and A is the area in mm2 Using Initial Temperature load, the finite element model showed an error of 1.15% in the top stresses with a decrease of 0.04MPa, but no difference was observed at the bottom face giving zero error.…”
Section: Numerical Modelingmentioning
confidence: 99%